Acridinium Benzoates for Ratiometric Fluorescence Imaging. Issue 15 (19th February 2020) - Wen, Min; Wang, Xijing; Wang, Ting; Sun, Yan; Fan, Mengting; Li, Min; Zhu, Junru; Zhang, Dazhi; Cui, Xiaoyan; Shan, Yongkui
Abstract: Acridinium benzoate was developed as a unique ICT‐based fluorescent scaffold for both ratiometric and turn‐on fluorescence imaging through decaging of the phenolic hydroxyl groups. Two fluorescent probes, Acr1‐H2 O2 and Acr1‐ β‐gal, were developed for the fluorescence imaging of H2 O2 and β‐galactosidase in vivo. Abstract : Ratiometric sensing : Acridinium benzoates with unique electrooptical properties were developed for ratiometric fluorescence imaging in vivo (see figure).